DESAIN DIKLAT PENDIDIK DAN TENAGA KEPENDIDIKAN PENDIDIKAN NONFORMAL - Supriyono Supriyono (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
Vast development occurs in the domain of Non Formal Education (NFE). It is in regards of educators, and its education personnel. They have to be professional in doing the job. In order to be professional, they have to undergo some preservice training followed by practice teaching. These trainings are vital to educators and educations personnel because trainings would be an opportunity to teach them to be role models, responsible, patient and to have empathy. Trainings consist of foundations of instructions and educational technology, managerial skills and teaching skills related to NFE context.